2016
DOI: 10.1016/j.nbd.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-dopa priming on cortical high beta and high gamma oscillatory activity in a rodent model of Parkinson's disease

Abstract: Prolonged L-dopa treatment in Parkinson’s disease (PD) often leads to the expression of abnormal involuntary movements known as L-dopa-induced dyskinesia. Recently, dramatic 80 Hz oscillatory local field potential (LFP) activity within the primary motor cortex has been linked to dyskinetic symptoms in a rodent model of PD and attributed to stimulation of cortical dopamine D1 receptors. To characterize the relationship between high gamma (70–110 Hz) cortical activity and the development of L-dopa-induced dyskin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 82 publications
8
62
0
Order By: Relevance
“…By now, the association between high-frequency LFP oscillations and LID has been verified in several independent studies. For example, Judie Walters’ lab has found that the power of cortical 80 Hz oscillations gradually increases as dyskinetic behaviors become more severe during a course of l -DOPA treatment (Dupre et al 2016). The link between narrowband gamma and LID is currently being explored at several levels (Delaville et al 2015; Belic et al 2016; Dupre et al 2016, 2015; Tamte et al 2016).…”
Section: Cortical Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…By now, the association between high-frequency LFP oscillations and LID has been verified in several independent studies. For example, Judie Walters’ lab has found that the power of cortical 80 Hz oscillations gradually increases as dyskinetic behaviors become more severe during a course of l -DOPA treatment (Dupre et al 2016). The link between narrowband gamma and LID is currently being explored at several levels (Delaville et al 2015; Belic et al 2016; Dupre et al 2016, 2015; Tamte et al 2016).…”
Section: Cortical Dynamicsmentioning
confidence: 99%
“…For example, Judie Walters’ lab has found that the power of cortical 80 Hz oscillations gradually increases as dyskinetic behaviors become more severe during a course of l -DOPA treatment (Dupre et al 2016). The link between narrowband gamma and LID is currently being explored at several levels (Delaville et al 2015; Belic et al 2016; Dupre et al 2016, 2015; Tamte et al 2016). Because cortical activity is under strong control of thalamic input, it is possible that an aberrant thalamic input could be driving fast cortical oscillations in LID (Dupre et al 2015).…”
Section: Cortical Dynamicsmentioning
confidence: 99%
“…Beta oscillations are viewed as normal for the resting or Bidling^state; their reduction with movement onset may play a role in allowing movement to take place. Conceivably increased or persistent beta-band oscillations could disrupt movement initiation and execution, or may reflect the underlying impairment of movement initiation or even be a compensatory mechanism [164].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…Similar results were obtained for 40 Hz and 80 Hz input frequencies in the case of low (red curve) and high (blue curve) firing rates of FSIs. Previous experimental work [17,39,57] has demonstrated the importance of 80 Hz corticostriatal oscillations for shaping neuronal interactions between cortex and striatum. Recently, it has been found that the FSIs Interplay between periodic stimulation and GABAergic inhibition in striatal network oscillations fire in relation to very high cortical frequencies [43].…”
Section: Propagation Of Cortical Oscillations In the Striatal Networkmentioning
confidence: 99%